Electrophoresis simulations using Chebyshev pseudo‐spectral method on a moving mesh. Issue 5 (23rd December 2021) - Bahga, Supreet Singh; Gupta, Prateek
Abstract: We present the implementation and demonstration of the Chebyshev pseudo‐spectral method coupled with an adaptive mesh method for performing fast and highly accurate electrophoresis simulations. The Chebyshev pseudo‐spectral method offers higher numerical accuracy than all other finite difference methods and is applicable for simulating all electrophoresis techniques in channels with open or closed boundaries. To improve the computational efficiency, we use a novel moving mesh scheme that clusters the grid points in the regions with poor numerical resolution. We demonstrate the application of the Chebyshev pseudo‐spectral method on a moving mesh for simulating nonlinear electrophoretic processes through examples of isotachophoresis (ITP), isoelectric focusing (IEF), and electromigration‐dispersion in capillary zone electrophoresis (CZE) at current densities as high as 1000 A/m 2 $^{2}$ . We also show the efficacy of our moving mesh method over existing methods that cluster the grid points in the regions with large concentration gradients. We have integrated the adaptive Chebyshev pseudo‐spectral method in the open‐source SPYCE simulator and verified its implementation with other electrophoresis simulators.